The acute scrotum in infancy: A retrospective regional study. Issue 2 (April 2022) - Coles, Vanessa; Elagami, Hesham; Bhandarker, Kailas; Awolaran, Gbenga; Murphy, Feilim; Yardley, Iain; Hallows, Ruth; Davenport, Mark
Summary: Introduction: Testicular torsion during infancy (<1 year) is known to be a rare event with relatively few studies on the subject in the published scientific literature. We reviewed the experience of infant scrotal exploration within a paediatric surgical network of four centres serving an approximate paediatric population of 1.8 million. Aim: To review current practice of scrotal explorations in infancy and explore areas for improvement. Method: Retrospective review of emergency operations for acute scrotum between January 2016 and December 2018. Data are presented as median (range) and compared using non-parametric tests. P < 0.05 was regarded as significant. Results: A total of 560 paediatric scrotal explorations were performed. Of these, 25 (4%) were under one year at the time of surgery, median 4 months (1 day-5 months) (Fig. 1). The most common diagnosis was "epididymitis" (11/25, 44%). Testicular torsion was found in 28% (7/25), increasing to 66% (4/6) in those under one month. Of those with confirmed testicular torsion, three (43%) underwent a primary orchiectomy with contralateral fixation and three (43%) detorsion and bilateral fixation, with all three cases found to have testicular atrophy at follow-up. The final case was of metachronous torsion, with the initial presentation not operated on and the subsequent presentation undergoing detorsion and fixation. This was the only case of testicular salvage in our series. There were no underlying urological issues in any patient and no reported complications or ongoing urological issues post-surgery. The rate of follow-up was 17/25 (68%). Conclusion: We present one of the only clinical series to focus on acute scrotum in the under one year old and not just the neonatal period. Testicular torsion remains a rare event in this age group but invariably leads to testicular loss. Summary Figure Causes of acute scrotum in infancy. Summary Figure